Ambivalence: A Key to Clinical Trial Participation? - Chilton, Janice A.; Rasmus, Monica L.; Lytton, Jay; Kaplan, Charles D.; Jones, Lovell A.; Hurd, Thelma C. (Frontiers in Oncology, 2018)
Introduction: Trust exerts a multidimensional influence at the interpersonal level in the clinical trials setting. Trust and distrust are dynamic states that are impacted, either positively or negatively, with each participant-clinical trials team interaction. Accepted models of trust posit that trust and distrust coexist and their effects on engagement and retention in clinical trials are mediated by ambivalence. Ambivalence is a normal and uncomfortable state in the complex decision making process that characterizes the recruitment and active treatment phases of the clinical trials experience. While understanding of trust has been informed by a robust body of work, the role of distrust and ambivalence in the trust building process are less well understood. The review was conducted to understand the constructs of ambivalence, its triggers and the contextual factors that might influence minority participation in oncology clinical trials. In addition, the researchers have sought to link theory to clinical intervention by investigating the feasibility and role of Motivational Interviewing in different stages of the clinical trials continuum. Methods: A search of the PubMed and Google Search databases was conducted by the authors. A total of 167 abstracts were reviewed and 68 of the corresponding papers were chosen for inclusion in this review. Results: Findings suggest that ambivalence can be processed and managed to enable a participant to generate a response to their ambivalence. Recognizing and managing triggers of ambivalence, and contextual factors related to the totality of one’s previous health-care experience are critical to our understanding of ambivalence. Motivational Interviewing has widespread applications in healthcare settings, which includes enabling participants to navigate in shared-decision making with their clinician, as well as executing changes in participant behavior. The Integrated Model of Trust can incorporate the role of therapeutic techniques like Motivational Interviewing in different stages of the clinical trials continuum. Conclusions: Ambivalence is a key component of clinical trial participation; like trust, ambivalence can be managed and plays a major role in the management of trust in interpersonal relationships over time. The management of ambivalence may play a major role in increasing clinical trial participation particularly among the marginalized or the vulnerable.